Factor 6x^2-7x-3



factor 6x^2-7x-3



The first thing you want is to represent this equation in another form where you can factor out terms. For that, you can write middle term " -7x " as " -9x+2x ". Now if you write equation again, it will be 6x^2-9x+2x-3=0. You can pull out 3x from the first 2 terms and 1 from the next 2. Now, the equation would be 3x(2x-3)+1(2x-3). "2x-3 " is common in this, pulling out 2x-3 gives you (2x-3)(3x+1)=0. Now either 2x-3=0 which gives you x=3/2 or 3x+1=0 which gives you x=-1/3. So the answer is x=3/2, -1/3